The effect of teacher trust in colleagues on collective teacher efficacy: Examining the mediating role of the characteristics of professional learning communities. (November 2022) - Ninković, Stefan; Florić, Olivera Knežević; Đorđić, Dejan
Abstract: It is important to identify factors that enable teacher collaborative activities and joint work. The study aimed to investigate the relationships between teacher trust in colleagues, dimensions of professional learning communities, and collective teacher efficacy. Data were collected from 362 Serbian teachers and analyzed using the techniques of structural equation modeling. The obtained results showed that teacher trust in colleagues has a direct effect on teachers' collective efficacy. Moreover, shared responsibility, as a component of professional learning communities, was a mediator in the relationship between teacher trust and collective teacher efficacy. Practical implications and limitations were discussed.